Nurses’ Perception about Medication Errors Types, Causes and Barriers to Report it (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Since there is a continuous rise in the number of patients requiring quantity of prescribedmedications and medical care, there is always an increasing requirement for a complete system that cancarefully evaluate all the medication errors that may occur.Objective: Determine types, causes, and barriers of medication errors reportSetting: The current study was conducted in Imam Sadiq Hospital - Babel City during 2019 yearSubjects: The study comprised of 100 nurses with at least two years of clinical experienceTools: The Medication Administration Errors (MAEs) method was used to gather the data by reportingruestionnaire that was formulated by Wakefield et al.(1996) and revised by the researchers. The questionnairehas 65 questions; 15 items are related to the reasons of medication errors occurrence, 7 items concerningthe reasons of not reporting medication errors and 5 items related to the percentage of each medicationerror type reported on units which classified into 9 items for non- intravenous and 11 items for intravenousmedication administration errors.Results: most of nurses reported no mistakes related to wrong route, wrong dose, wrong method;Whilewrong time, allergic reaction and infusion rate mistakes were more repetitive errors accordingto their perception. Fears about punishmentand from patient relatives was most common barriers to reportmedicationerrors.Conclusion: Medication errors is highly priority health system problem; more than half of nurses reportedno mistakes related to wrong dose, wrong method, and wrong patient, most of them indicated that no clearlydefinition of medication error was identified, unclear reporting system wasexisted.Recommendations Assessment and surveillance system should be followed to minimize medication errorspotentiality. Nurses have to always remember that they are responsible and accountable to the results of theirdecisions andactions whatever they are.
Keywords: Medication, errors, causes, types.